THE INTEGRATION OF ISLAMIC CROWDFUNDING IN MEASURING THE SME’S SUSTAINABILITY IN SELANGOR - Al Sarah Alyaa Al Buhari; Noraini Farhana Mohd Zulhairi; Abdul Aziz Zakaria; Azrif Nizam Mhd Razak; Nur Amira Husna Hasrin; Norasekin Abd Rashid; Sara Shakira Shari (Journal of Islamic, Social, Economics and Development, 2023)
Small and Medium-Sized Enterprises (SMEs) are one of the largest contributors to the economy of Malaysia and they can be categorized as non-subsidiary, local companies that employ fewer than several employees. However, SMEs face a problem with how to sustain the economy. Thus, this study aims to examine whether technology adoption, competitive advantage, financial literacy skills, and Islamic crowdfunding affect SMEs’ sustainability. Two types of data collection were used in this study which are primary and secondary data. A self-administrated questionnaire is used to collect the primary data with a total number of 259 respondents received from SMEs in Selangor. The data were analysed by using descriptive analysis and correlation analysis. The findings show that Islamic crowdfunding has the strongest relationship (r = .521) followed by competitive advantage with (r = .497), technology adoption with (r = .433), and financial literacy skills with (r = .377) All identified factor shows a significant relationship with SMEs sustainability with (p = .000). The sustainability of SMEs is essential to be developed to ensure the economy continues to grow. Therefore, this study helps SMEs consider Islamic Crowdfunding as one of the tools to sustain their business industry.